THE ROLE OF AN OTOLARYNGOLOGIST IN MAINTAINING HEARING AND RESPIRATORY HEALTH (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Otolaryngology, also known as ENT (ear, nose, and throat) medicine, is a specialized field of medicine focused on the diagnosis, treatment, and prevention of diseases related to the ear, nose, throat, and related structures of the head and neck. Otolaryngologists, also known as ENT specialists, play a critical role in maintaining the health of the auditory and respiratory systems. The focus of this article is to explore how otolaryngologists contribute to preserving hearing and respiratory health through a variety of diagnostic methods, medical treatments, and surgical interventions. Hearing and respiratory disorders can significantly impact a patient's quality of life, and early diagnosis and appropriate intervention by an otolaryngologist are essential in preventing further complications. This article reviews the most common conditions treated by otolaryngologists and examines the most recent advancements in treatment strategies for hearing and respiratory health, providing a detailed exploration of diagnostic methods, treatments, results, and relevant literature.